Narratives, Symbols, and Rituals: Oral Tradition in Indigenous Resistance to Development Structuralism in West Papua, Indonesia - Rupiassa, Dominggus Alexander Agusto; Lattu, Izak Y. M; Therik, Wilson M.A (Jurnal Sosiologi Reflektif, 2024)
Development projects that disregard Indigenous rights often provoke resistance, particularly in West Papua, Indonesia, where the Indigenous Kaimana people uniquely employ covert resistance through oral traditions to safeguard their rights. This study aims to understand how the Kaimana Indigenous community utilizes orality as a form of resistance against developmental structuralism. Employing a realist ethnographic method, this research directly observes the daily lives of the Indigenous community and documents forms of hidden resistance embedded in their oral traditions. Data were collected through in-depth interviews, focus group discussions (FGDs), observation, and documentary analysis of symbolic resistance activities. The findings reveal that Kaimana's Indigenous resistance is conveyed through three principal elements: storytelling, symbolism, and ritual. First, storytelling serves as a medium of resistance by recounting their spiritual connection to nature as a way of upholding ancestral rights. Second, symbols such as bamboo and sago leaves are used in road blockades, representing life and resistance. Third, traditional rituals involving everyday symbols are believed to possess mystical power and are used to protect Indigenous lands. These three elements illustrate that while the Kaimana community does not wholly oppose development, they demand that their customary rights be respected throughout the process. Pembangunan yang mengabaikan hak-hak masyarakat adat sering kali memicu resistensi, terutama di wilayah Papua Barat, Indonesia, di mana masyarakat adat Kaimana memiliki cara unik dalam mempertahankan hak mereka melalui resistensi tertutup berbasis Oral Traditions. Penelitian ini bertujuan untuk memahami bagaimana masyarakat adat Kaimana menggunakan kelisanan sebagai bentuk perlawanan terhadap strukturalisme pembangunan. Dengan menggunakan metode etnografi realis, penelitian ini mengamati langsung kehidupan sehari-hari masyarakat adat dan mendokumentasikan bentuk-bentuk perlawanan yang tersembunyi dalam tradisi lisan. Data dikumpulkan melalui wawancara mendalam, diskusi kelompok terfokus (FGD), observasi, dan studi dokumentasi terkait aksi perlawanan simbolis. Hasil penelitian menunjukkan bahwa resistensi masyarakat adat Kaimana dilakukan melalui tiga elemen utama: cerita, simbol, dan ritual. Pertama, cerita menjadi sarana perlawanan dengan mengisahkan hubungan spiritual mereka dengan alam sebagai cara mempertahankan hak leluhur. Kedua, simbol-simbol seperti bambu dan daun sagu digunakan dalam aksi pemalangan sebagai lambang kehidupan dan perlawanan. Ketiga, ritual adat yang melibatkan simbol-simbol sehari-hari dianggap memiliki kekuatan magis dan digunakan untuk melindungi wilayah adat. Ketiga elemen ini memperlihatkan bahwa masyarakat adat Kaimana tidak sepenuhnya menolak pembangunan, namun menuntut agar hak-hak adat mereka dihormati dalam proses tersebut.